1996
DOI: 10.1016/s0969-2126(96)00149-9
|View full text |Cite
|
Sign up to set email alerts
|

The structure of glucose-fructose oxidoreductase from Zymomonas mobilis: an osmoprotective periplasmic enzyme containing non-dissociable NADP

Abstract: In GFOR, the NADP is found associated with a classical dinucleotide-binding domain in a conventional fashion. The NADP is effectively buried in the protein-subunit interior as a result of interactions with the N-terminal arm from an adjacent subunit in the tetramer, and with a short helix from the C-terminal domain of the protein. This accounts for NADP's inability to dissociate. The N-terminal arm may also contribute to stabilization of the tetramer. The enzyme has an unexpected structural similarity with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 70 publications
1
115
0
Order By: Relevance
“…2a) demonstrates that these two proteins superimpose with a rootmean-square deviation of 2.0 Å for 307 structurally equivalent ␣-carbons, which is remarkable given their limited amino acid sequence identity of ϳ13% (16). It has been postulated that Lys-129 and Tyr-217 are involved in the catalytic mechanism of the oxidoreductase (13). These residues correspond to Trp-123 and His-214 in KlGal80p.…”
Section: Resultsmentioning
confidence: 87%
“…2a) demonstrates that these two proteins superimpose with a rootmean-square deviation of 2.0 Å for 307 structurally equivalent ␣-carbons, which is remarkable given their limited amino acid sequence identity of ϳ13% (16). It has been postulated that Lys-129 and Tyr-217 are involved in the catalytic mechanism of the oxidoreductase (13). These residues correspond to Trp-123 and His-214 in KlGal80p.…”
Section: Resultsmentioning
confidence: 87%
“…Especially AAOR catalyzes also the reactions of a panel of different sugars. 4,5 GP6D is more specific, it catalyses oxidation (dehydrogenation) of D-glucose-6-phosphate to 6-phospho-D-glucono-1,5-lactone. 1 AFR reduces C2 carbon of 1,5-anhydro-Dfructose, the central intermediate of the anhydrofructose pathway.…”
Section: Catalyzed Reactionsmentioning
confidence: 99%
“…Site-directed mutagenesis and X-ray crystallographic studies [46,47] have revealed that this enzyme has a typical dinucleotide-binding domain, i.e. a Rossmann (β-α-β) fold [48] with a fingerprint sequence, an N-terminal Gly-Xaa-Gly-Xaa-Xaa-Ala sequence and a Glu-Lys-Pro motif for interaction with the carboxamide group of the nicotinamide ring and the nicotinamide ribose.…”
Section: Alignment Of Dimeric Dds With Other Proteinsmentioning
confidence: 99%
“…However, because the secondary structures of the proteins listed in Figure 2 predicted the β-α-β-fold around the N-terminal regions from Gly-6 to Gly-11 of dimeric DDs (results not shown), it is possible that dimeric DD also has a coenzymebinding domain composed of the N-terminal β-α-β fold and the Glu-Lys-Pro motif. However, the substrate-binding domain of GFO has not been elucidated but two residues, Tyr-217 and Tyr-296, have been proposed as candidates for the catalytic residue on the basis of the three-dimensional structure of the enzyme [47]. Of these, only Tyr-217 is conserved at position 180 of dimeric DDs and the proteins in Figure 2, but is not present in the other proteins listed in Table 3.…”
Section: Alignment Of Dimeric Dds With Other Proteinsmentioning
confidence: 99%